A Survey on Reduction in Energy Consumption by Improved AODV on Mobile Ad Hoc Network - keer, Vinita; Ali, Syed Imran (International Journal of Computer Sciences and Engineering, 2025)
A MANET consists number of mobile devices form a network together without any centralized coordinator. In this network device changes location and organize itself, connected by wireless link. Ad hoc network is temporary plug in connection for a small session. Due to mobility of nodes or devices dynamically forming a momentary network. It doesn’t have infrastructure because these are useful for temporary connection, so that there is a possibility of a lacking in a permanent source of energy, because the entire independent mobile device are entirely dependent on battery power. Energy consumption is one of the important factors in case of mobile node. Less amount of energy or lack of battery power is directly affect the life time of network. This paper is discussion improvement the lifetime of the path. In ad hoc network some of the energy efficient protocols are: AODV, OLSR, DSR, and DSDV.